Cisoid-cis intermediate plays a crucial role in decolouration rate in photochromic reaction of 8H-pyranoquinazolines and 3H-naphthopyrans. (May 2022) - Brazevic, Sabina; Sikorski, Marek; Sliwa, Michel; Abe, Jiro; Rode, Michał F.; Burdzinski, Gotard
Abstract: The photochromic reaction of 8 H -pyranoquinazoline shows intriguing aspects in comparison to 3 H -naphthopyrans. These come from a stabilized excited singlet state for 8 H -pyranoquinazoline, which has a longer lifetime and is strongly sensitive to the solvent. The polar solvent acetonitrile reduces the quantum yield of coloured isomer formation ( transoid - cis species). Colour fading related to the decay of transoid - cis population is faster than that for 3 H -naphthopyran family and occurs within few seconds time-window in solution at room temperature. Theoretical calculations show the crucial role in fading process played by the potential energy landscape, with the cisoid-cis intermediate located in a shallow high-energy minimum. Highlights: 8 H -pyranoquinazoline's photochromic quantum yield depends on solvent polarity. Transoid - cis thermal fading is a two-step process with a reversible first step. Dissymmetrical substitution in 3-aryl rings leads to complex decolouration kinetics. Methoxy group at the position 10 suppresses transoid-trans form generation.